HBR's 10 must reads on teams, - Harvard business School (HBR's 10 must reads series, 2013)
Leading experts such as Jon Katzenbach, Teresa Amabile, and Tamara Erickson provide the insights and advice you need to:Boost team performance through mutual accountability. Motivate large, diverse groups to tackle complex projects. Increase your teams’ emotional intelligence. Prevent decision deadlock. Extract results from a bunch of touchy superstars. Fight constructively with top-management colleagues